Answer:
we can say that f and g are inverses of each other because f(g(x)) = x and g(f(x)) = x
Explanation:
We need to confirm that f and g are inverses by showing that f(g(x)) = x and g(f(x)) = x.
We have
![f(x)= (8)/(x)\\g(x)=(8)/(x)](https://img.qammunity.org/2022/formulas/mathematics/high-school/le0xb811lwmd2atfke4fuwgs6ado5e1gml.png)
Now, finding f(g(x))
Put x = 8/x in f(x)
![f(g(x)) =(8)/((8)/(x) )\\=8/ (8)/(x)\\=8 * (x)/(8)\\=x](https://img.qammunity.org/2022/formulas/mathematics/high-school/dcpq1v4xrr1g97wdwqvyxhhku40whjaru6.png)
So, we get f(g(x))=x
Now, find g(f(x))
Put x = 8/x in g(x)
![g(f(x)) =(8)/((8)/(x) )\\=8/ (8)/(x)\\=8 * (x)/(8)\\=x](https://img.qammunity.org/2022/formulas/mathematics/high-school/lh84018c8yishd0xc1fnb7uq5he2edxs8u.png)
So, we get g(f(x)) = x
Therefore we can say that f and g are inverses of each other because f(g(x)) = x and g(f(x)) = x